2012
DOI: 10.1016/j.bbamem.2012.04.018
|View full text |Cite
|
Sign up to set email alerts
|

trans Arachidonic acid isomers inhibit NADPH-oxidase activity by direct interaction with enzyme components

Abstract: NADPH-oxidase is an enzyme that represents, when activated, the major source of non-mitochondrial reactive oxygen species. In phagocytes, this production is an indispensable event for the destruction of engulfed pathogens. The functional NADPH-oxidase complex consists of a catalytic membrane flavocytochrome b (Cytb(558)) and four cytosolic proteins p47(phox), p67(phox), Rac and p40(phox). The NADPH-oxidase activity is finely regulated spatially and temporally by cellular signaling events that trigger the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 72 publications
3
23
0
1
Order By: Relevance
“…Subcellular fractionation of yeast cells 0.7 ml of total membrane fractions containing 1.5e6 mg/ml membrane proteins was loaded on top of a discontinuous sucrose gradient as described in Ref. [22]. Briefly, in an SW32 centrifuge tube 3.7 ml of STE 60 (60% sucrose), STE sucrose, 20 mM TriseHCl (pH 7.4), 1 mM EDTA, 1 mM NaN 3 ).…”
Section: Relipidation Of Recombinant Cytb 558mentioning
confidence: 99%
“…Subcellular fractionation of yeast cells 0.7 ml of total membrane fractions containing 1.5e6 mg/ml membrane proteins was loaded on top of a discontinuous sucrose gradient as described in Ref. [22]. Briefly, in an SW32 centrifuge tube 3.7 ml of STE 60 (60% sucrose), STE sucrose, 20 mM TriseHCl (pH 7.4), 1 mM EDTA, 1 mM NaN 3 ).…”
Section: Relipidation Of Recombinant Cytb 558mentioning
confidence: 99%
“…By contrast, the endogenous PMA analog diacylglycerol acts transiently because of its fast metabolism (41). Nox2 has been shown to be activated by cis-unsaturated fatty acids but not by trans-unsaturated or saturated ones (8,42). Indeed, oleic acid activated the Nox2-based oxidase reconstituted in CHO cells (Fig.…”
Section: Phoxmentioning
confidence: 99%
“…The study shows that p67phox integrity is crucial for the oxidase activity and that irradiation of p67phox drastically decreases its interaction with arachidonic acid (AA) and destabilizes the p47phox-p67phox complex (93,110). The precise role played by AA still remains unclear, though Souabni et al have shown that trans-arachidonic acid (trans-AA), in contrast to cis-AA, cannot activate the NADPH oxidase but is able to inhibit cis-AA-activated generation of O 2 -through a direct interaction with p67phox and with the membrane fraction, probably indirectly via modification of the membrane physical properties (138).…”
Section: Direct Regulation Of Activity For the Nox2 Systemmentioning
confidence: 99%